Identifying and quantifying secondhand smoke in source and receptor rooms: logistic regression and chemical mass balance approaches. (23rd May 2013) - Dacunto, P. J.; Cheng, K.‐C.; Acevedo‐Bolton, V.; Jiang, R.‐T.; Klepeis, N. E.; Repace, J. L.; Ott, W. R.; Hildemann, L. M.
Abstract Identifying and quantifying secondhand tobacco smoke (SHS) that drifts between multiunit homes is critical to assessing exposure. Twenty‐three different gaseous and particulate measurements were taken during controlled emissions from smoked cigarettes and six other common indoor source types in 60 single‐room and 13 two‐room experiments. We used measurements from the 60 single‐room experiments for (i) the fitting of logistic regression models to predict the likelihood of SHS and (ii) the creation of source profiles for chemical mass balance (CMB) analysis to estimate source apportionment. We then applied these regression models and source profiles to the independent data set of 13 two‐room experiments. Several logistic regression models correctly predicted the presence of cigarette smoke more than 80% of the time in both source and receptor rooms, with one model correct in 100% of applicable cases. CMB analysis of the source room provided significant PM2.5 concentration estimates of all true sources in 9 of 13 experiments and was half‐correct (i.e., included an erroneous source or missed a true source) in the remaining four. In the receptor room, CMB provided significant estimates of all true sources in 9 of 13 experiments and was half‐correct in another two.